Intralymphatic Immunotherapy (ILIT) With Bee Venom Allergens: A Clinical Proof-of-Concept Study and the Very First ILIT in Humans - Chabot, Alexandra; Senti, Gabriela; Erdmann, Iris; Prinz, Bettina M.; Wüthrich, Brunello; Šošić, Lara; Kündig, Thomas M.; Johansen, Pål (Frontiers in Allergy, 2022)
Background: Subcutaneous venom immunotherapy (VIT) represents an effective treatment against bee venom allergy. However, it involves long treatment times, high costs, low compliance, and risk of adverse events (AEs). Shorter, safer, and cheaper treatment options are therefore pursued. Objective: To determine the safety, immunogenicity, and efficacy of bee venom intralymphatic immunotherapy (ILIT). Methods: In one open pilot study, 12 patients received bee venom ILIT in three sessions with 14 days intervals: 0.1 to 5 µg per dose. Ultrasound imaging was applied to guide injection and to document lymph node structure. In a second study, 67 patients from 15 centers in Europe and Australia were randomized to receive four doses of either 10 or 20 µg bee venom ILIT with 28 days intervals. Clinical endpoints included specific IgE and IgG and protection after a bee sting challenge. Results: In the proof-of-concept study, no serious AEs were observed. An increase in allergen-specific IgG1, but not IgG4 and IgE was observed. ILIT induced protection against a bee sting challenge in 7 out of 8 challenged patients. In the multicenter study, an increase in allergen-specific IgG, but also IgE was observed, with highest increase in patients receiving the higher ILIT dose. Due to numerous serious AEs after a bee sting challenge, the study was terminated early. However, out of 45 patients challenged, 15 (65%) and 18 (82%) patients in the 10- and 20-µg groups, respectively, showed an improvement of two grades or more. No correlation was observed between antibody levels and string protection. Conclusions: While the pilot study suggested safety and efficacy of bee venom ILIT, the high number of AEs seen after the sting challenge following the randomized study suggested that the immunological protection offered by bee venom ILIT is insufficient. Of note, the bee venom allergen extract used in the two studies were from two different providers. While the first study used a formulation approved for use in subcutaneous VIT, the second study used a non-approved formulation never tested in humans. Further studies with approved formulations should be performed to generate conclusive results regarding the safety and efficacy of bee venom ILIT.